Effects of subtypes of adrenergic and angiotensinergic antagonists on the water and sodium intake induced by adrenaline injected into the paraventricular nucleus - Carnargo, LAD; Saad, W. A.; Cerri, Paulo Sérgio [UNESP]; Camargo, GMPD (Elsevier B.V., 2003)
The present experiments were conducted to investigate die role of the alpha(1A)-, alpha(1B)-, beta(1)-, beta(2)-adrenoceptors, and the effects of losartan and CGP42112A (selective ligands of the AT(1) and AT(2) angiotensin receptors, respectively) on the water and sodium intake elicited by paraventricular nucleus (PVN) injection of adrenaline. Male Holtzman rats with a stainless steel cannula implanted into the PVN were used. The ingestion of water and sodium was determined in separate groups submitted to water deprivation or sodium depletion with the diuretic furosemide (20 mg/rat). 5-Methylurapidil (an alpha(1A)-adrenergic antagonist) and ICI-118,551 (a beta(2)-adrenergic antagonist) injected into the PVN produced a dose-dependent increase, whereas cyclazosin (an alpha(1B)-adrenergic antagonist) and atenolol (a beta(1)-adrenergic antagonist) do not affect the inhibitory effect of water intake induced by adrenaline. on the other hand, the PVN administration of adrenaline increased the sodium intake in a dose-dependent manner. Previous injection of the alpha(1A) and beta(1) antagonists decreased, whereas injection of the alpha(1B) and beta(2) antagonists increased the salt intake induced by adrenaline. In rats with several doses of adrenaline into PVN, the previous administration of losartan increased in a dose-dependent manner the inhibitory effect of adrenaline and decreased the salt intake induced by adrenaline, while PVN CGP42112A was without effect. These results indicate that both appetites are mediated primarily by brain AT(1) receptors. However, the doses of losartan were more effective when combined with the doses of CGP42112A than given alone p < 0.05, suggesting that the water and salt intake effects of PVN adrenaline may involve activation of multiple angiotensin II (ANG II) receptors subtypes. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: alpha- and beta-adrenergic antagonists; AT(1) and AT(2) antagonists; water intake; sodium intake; paraventricular nucleus